Chronic Inflammatory Periodontal Disease in Patients with Human Immunodeficiency Virus. - Vania López Rodríguez; Emilio Carpio Muñoz; Vicente Fardales Macías; Iralys Benítez Guzmán (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: The Chronic Inflammatory Periodontal Disease is related with multiple risk factors. Those patients with human immunodeficiency virus have higher risk of presenting this disease and it is usually more serious in these cases. Objective: To describe the prevalence of Chronic Inflammatory Periodontal Disease in patients with HIV. Methods: Descriptive, observational, cross-sectional study including patients with HIV in Sancti Spiritus province. The occurrence of the disease was determined after the Periodontics Cuban Standards, and oral hygiene was assessed through the simplified oral hygiene index. Other variables were measured, such as smoking habits, T CD4+ lymphocyte counting and virus load. The independent association of each risk factor with the disease was determined through a logistic regression model. Results: The 56, 5 % of the 154 patients presented Chronic Inflammatory Periodontal Disease; 60 (39.0%) gingivitis and 27 (17,5%) periodontitis. Gingivitis was associated with poor oral hygiene (OR: 3,71) and periodontitis with smoking habit (OR: 5,20). The severe forms of periodontitis occurred mainly in patients with lymphocyte counting lower than 500 cells/mm3 . Conclusions: The prevalence of Chronic Inflammatory Periodontal Disease in patients with HIV in Sancti Spiritus province is linked to known risk factors such as smoking habits and oral hygiene.